2019
DOI: 10.1016/j.ajpath.2019.06.004
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of High Glucose–Induced Lysyl Oxidase Propeptide on Retinal Endothelial Cell Survival

Abstract: Diabetic retinopathy (DR) is characterized by apoptotic cell loss in the retinal vasculature. Lysyl oxidase propeptide (LOX-PP), released during LOX processing, has been implicated in promoting apoptosis in various diseased tissues. However, its role in the development and progression of DR is unknown. We investigated whether high glucose (HG) or diabetes alters LOX-PP expression and thereby influences AKT pathway and affects retinal endothelial cell survival. Rat retinal endothelial cells were grown in normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Hyperglycemia can initiate many biochemical changes in the retinal microvasculature, including increased oxidative stress in the polyol pathway, protein kinase C (PKC) activation, and advanced glycation end-product formation [61] (Figure 3). Rat retinal endothelial cells exposed to high glucose (HG) showed a down-regulation of the protein kinase B (also known as AKT) pathway and increased apoptosis [62]. HG was also found to increase mitochondrial fragmentation and pro-apoptotic cytochrome c levels in vascular cells of rat retinal capillaries [63,64].…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…Hyperglycemia can initiate many biochemical changes in the retinal microvasculature, including increased oxidative stress in the polyol pathway, protein kinase C (PKC) activation, and advanced glycation end-product formation [61] (Figure 3). Rat retinal endothelial cells exposed to high glucose (HG) showed a down-regulation of the protein kinase B (also known as AKT) pathway and increased apoptosis [62]. HG was also found to increase mitochondrial fragmentation and pro-apoptotic cytochrome c levels in vascular cells of rat retinal capillaries [63,64].…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…There was no difference in the LOX levels of vitreous samples derived from male and female subjects in both the diabetic group and the non-diabetic group. Of note, our recent study indicated that mannitol used as osmotic control showed no effects on LOX levels in retinal endothelial cells in vitro [34].…”
Section: Resultsmentioning
confidence: 99%
“…In CDAA-induced NASH model, our rst observations indicated that LOXL1 were strongly expressed in activation HSCs and also in endothelial cells positioned between the plates of hepatocytes, suggested that abnormal expression of LOXL1 was different from the CCl 4 induced brosis model. Many reports indicate that LOX or LOXL2 predominantly expressed in HSCs, but also expressed in injured hepatocytes or endothelial cells under pathological conditions (13,(19)(20)(21), especially under metabolic disorders condition. We speculated that different etiology of the liver diseases would display differences in the expression patterns of LOXL1.…”
Section: Discussionmentioning
confidence: 99%